Theoretical Research of Properties of Paraboloid surfaces with the Purpose of Substantiation of the Optimal Method of Adjustment of the Facets of the Concentrator - Avchiev, Shukhrat; Khusnora, Juraeva; Tagaeva, Dilafruzkhon; Xamidova , Maknona; Yuldashev, Akmaljon (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the properties of the relative positions of normals to a paraboloid surface. Theoretically, the existence of a region of minimum size in which all normals and a paraboloid intersect is found, and formulas for calculating the size and location of this region are obtained.